MPPT Control for Wind Energy Conversion System Based on a T-S Fuzzy - Abdennasser Benkada; H. Chaikhy; M. Monkade (Institute of Advanced Engineering and Science, 2018)
In this paper, we focus on the modeling and control of a wind power system based on a Permanent Magnet Synchronous Generator (PMSG). We proposed a technique of control strategies to have the maximum power from wind turbine (WT). This study deals with the problem of Maximum Power Point Tracking (MPPT) based on Takagi Sugeno fuzzy model. The stability analysis is achieved. The gains of the designed controller are calculated by solving Linear Matrix Inequality (LMI). Finally, simulation results are provided to demonstrate the validity and the effectiveness of the proposed method.